EFFECTS OF OSMOPRIMING ON GERMINATION, VIGOUR AND HEALTH OF Silybum marianum (L.) Gaertn. SEEDS - Agnieszka Rosińska; Hanna Dorna; Dorota Szopińska (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
Priming is one of the most common methods improving seed quality. The purpose of the research was to study effects of osmopriming on milk thistle seed germination, vigour, health and location of fungi at 10 and 20°C. Seeds (achenes) of two samples (I, II) were primed in the polyethylene glycol (PEG) solutions of osmotic potentials of -1.0, -1.25 and -1.5 MPa, at 15°C for 3, 5 and 7 days. Applied variants of priming improved energy of seed germination and germination capacity at 10°C in both samples. Enhancement of these parameters was also observed at 20°C, if seeds of sample I were primed in the PEG solutions of osmotic potentials of -1.0 MPa for 7 days and -1.25 and -1.5 MPa for 5 and 7 days. Priming, regardless of time and osmotic potential of PEG, accelerated seed germination at 10 and 20°C in both samples. Fungi of genera: Alternaria, Cladosporium, Fusarium and Rhizopus were frequently identified on the seeds. After priming significantly increased seed infestation with fungi, especially in sample I. The fungi were more often detected in pericarps and seed coats than embryos. Many a time, after priming an increase in inner achene infestation was observed.